Life cycle assessment of New Jersey offshore wind - M. Smith; N. Shoaib; P. Lal; P. Lal (Wind Energy Science)
As offshore wind gains momentum within US (United States) renewable energy goals, New Jersey's ambitious targets for offshore wind development represent a significant opportunity to reduce emissions and transition towards cleaner energy sources. This study presents a life cycle assessment (LCA) of a planned offshore wind farm off of New Jersey's coast, emphasizing the implications of a domestic supply chain. Key findings suggest that the offshore wind farm is projected to produce 0.013 kg CO2 kWh−1 of electricity generated, reflecting a 98 % decrease in carbon emissions compared to natural-gas-derived electricity. Further, when compared to carbon emissions from other renewable energy technologies, offshore wind outperforms both solar and onshore wind by 79 % and 43 %, respectively. This finding highlights offshore wind's role in greenhouse gas (GHG) emissions reduction through decarbonizing the electricity generation sector. This role is reinforced through the case of a domestic supply chain, a necessary factor in the mitigation of transportation-related impacts, like fuel combustion, to decrease emissions. Beyond GHG emissions, results indicate that the steel-intensive materials used in turbines and infrastructure contribute heavily to toxicity-related impacts, highlighting a need to seek alternative, lower-impact materials. This research underscores the potential of offshore wind to reduce greenhouse gas emissions and offers insight into the environmental dynamics and improved environmental-impact-based decision making to improve offshore wind deployment in the US.